1990
DOI: 10.1159/000171269
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Opioids, the Enteric Nervous System and Gut Motility

Abstract: Opium alkaloids have been used for centuries as potent antidiarrheals and analgesics, their constipating action in the latter instance taken as an unwanted effect. It was only during the last decade that the physiological role of opioid peptides present in both neurons and endocrine cells of the gastrointestinal (GI) tract has been defined. The recognition of distinct opioid receptor types which may be differentially involved in the control of motility, acid and electrolyte secretion in the GI tract presently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 25 publications
(31 reference statements)
0
23
0
1
Order By: Relevance
“…Given the overlapping complement of neurotransmitters in the CNS and ENS (Hansen, 2003), we hypothesized that it would potentially alter enteric neurotransmission as well. Indeed, receptors for plant-derived psychotropic drugs such as the cannabinoids or opioids are present in the ENS and mediate gastrointestinal function (Pertwee, 2001;Kromer, 1990). Although Cassia siamea plant preparations have been traditionally used as laxative drugs, the barakol extract has never been assessed for laxative activity.…”
Section: Discussionmentioning
confidence: 99%
“…Given the overlapping complement of neurotransmitters in the CNS and ENS (Hansen, 2003), we hypothesized that it would potentially alter enteric neurotransmission as well. Indeed, receptors for plant-derived psychotropic drugs such as the cannabinoids or opioids are present in the ENS and mediate gastrointestinal function (Pertwee, 2001;Kromer, 1990). Although Cassia siamea plant preparations have been traditionally used as laxative drugs, the barakol extract has never been assessed for laxative activity.…”
Section: Discussionmentioning
confidence: 99%
“…Both inhibitory and excitatory enteric neurons may express OPRs (De Luca and Coupar, 1996). Immunoreactivities for at least some of the cognate endogenous ligands for these receptors, dynorphin and the enkephalins, are expressed in neurons and nerve fibers in either the myenteric or submucosal plexuses along the length of the intestinal tract (Kromer, 1990).…”
mentioning
confidence: 99%
“…Consistent with our data, Molina et al [21] showed that morphine levels in the brain were increased in septic rats. Furthermore, three main classes of opioid receptor exist in the mucosa of the gastrointestinal tract [22]. Hence, it is not implausible for endogenous morphine to increase gut mucosal protein turnover.…”
Section: Discussionmentioning
confidence: 99%